Protective effect of Momordica charantia fruit extract on hyperglycaemia-induced cardiac fibrosis - Abas, Razif; Othman, Faizah; Zar, Chi Thent (Hindawi Publishing Corporation, 2014)
In diabetes mellitus, cardiac fibrosis is characterized by increase in the deposition of collagen fibers. The present study aimed to observe the effect of Momordica charantia (MC) fruit extract on hyperglycaemia-induced cardiac fibrosis. Diabetes was induced in the male Sprague-Dawley rats with a single intravenous injection of streptozotocin (STZ). Following 4 weeks of STZ induction, the rats were subdivided (n = 6) into control group (Ctrl), control group treated with MC (Ctrl-MC), diabetic untreated group (DM-Ctrl), diabetic group treated with MC (DM-MC), and diabetic group treated with 150 mg/kg of metformin (DM-Met). Administration of MC fruit extract (1.5 g/kg body weight) in diabetic rats for 28 days showed significant increase in the body weight and decrease in the fasting blood glucose level. Significant increase in cardiac tissues superoxide dismutase (SOD), glutathione contents (GSH), and catalase (CAT) was observed following MC treatment. Hydroxyproline content was significantly reduced and associated morphological damages reverted to normal. The decreased expression of type III and type IV collagens was observed under immunohistochemical staining. It is concluded that MC fruit extract possesses antihyperglycemic, antioxidative, and cardioprotective properties which may be beneficial in the treatment of diabetic cardiac fibrosis.